(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2023)
A propagation strategy for piñuelo mangrove Pelliciera rhizophorae tested in the Cojimíes River estuary, Manabí province, coast of Ecuador is presented. The sectors of Guillermina, Uleam and Siberia were selected, and population densities were established. The Siberia and Guillermina sectors were selected for the collection of mature and germinated seeds; as well as sludge for the propagation of the piñuelo mangrove in the Uleam sector. The Siberia sector stands out as a natural nursery, due to the largest population of adult piñuelo mangroves, seedlings and germinated seeds. According to the propagation method through the nursery phase and direct sowing, a sustainable growth and survival of 95% is reflected at a density of 0.32 plants/m2 in 407.7m2; It was also observed that growth is favored in shaded spaces with 39.93 ±17.99 cm; compared to those exposed to the sun directly with an average height of 29.46 ±15.36cm. Other strategies applied included sludge application, controlled pruning and a site with access to the tidal regime. This planting modality is the first to be carried out in Ecuador with Pelliciera rhizophorae and the second in the same sector as reforestation experiences of this threatened species.